Mapping the nutritional value of diets across Europe according to the Nutri-Score front-of-pack label - Mertens, Elly; Peñalvo, José L. (Frontiers in Nutrition, 2023)
Background Front-of-pack labels, such as Nutri-Score, aim to offer clear information on the overall nutritional quality of foods and beverages to consumers, allowing them to make healthier food choices. Using the European Food Safety Authority (EFSA) Comprehensive European Food Consumption Database, the present study aims to map out European food consumption patterns by applying the Nutri-Score as a benchmark for nutritional value. Methods Country-specific food consumption data, collected by multiple 24-h dietary recalls or food records available from EFSA, were linked to the Dutch Food Composition Database (NEVO). Foods and beverages consumed by adolescents (10–17 years), adults (18–64 years), and the elderly (65–74 years) were graded following the modified Food Standard Agency Nutrient Profiling System (FSAm-NPS) and classified according to Nutri-Score grading, from A to E. Subsequently, a dietary index score (FSAm-NPS-DI) was calculated for each country-specific diet by age-groups and sex as an energy-weighted mean of the FSAm-NPS score of all foods and beverages consumed, with lower scores for a diet of greater overall nutritional quality. Results On average, the daily energy intake of adults across the European countries studied is distributed in 27.6% of A-, 12.9% of B-, 17% of C-, 30.0% of D-, and 12.5% of E-classified foods and beverages. This energy distribution, according to the Nutri-Score, corresponded to a median FSAm-NPS-DI score of 6.34 (interquartile range: 5.92, 7.19). For both adult males and females, Estonia reported the highest energy share from A-classified products, scoring the lowest on the FSAm-NPS-DI. On the other hand, Latvia reported the highest energy share from E-classified products, along with the highest FSAm-NPS-DI. Females and the elderly group reported, in general, a greater energy share from A- and a lower share from E-classified products, and had the lowest FSAm-NPS-DI scores. No sex-related difference was observed for adolescents whose share of energy was predominantly from A- and D-classified products, such as for adults and the elderly. Conclusion Our analyses leveraging the secondary use of country-specific databases on dietary intakes found considerable variation in the nutritional value of European diets, with an overall agreement across all countries on a modestly healthier dietary profile for the elderly and among females.